Evolution of the structures and magnetic properties of the manganese dicarboxylates, Mn2(CO2(CH2)nCO 2)(OH)2 and Mn4(CO2(CH 2)nCO2)3(OH)2 - Saines, P; Jain, P; Cheetham, A (2011)

(untitled)
Two new series of basic Mn dicarboxylate frameworks, Mn2(CO 2(CH2)nCO2)(OH)2 (where n = 0, 2, 4 and 5) and Mn4(CO2(CH2) nCO2)3(OH)2 (where n = 3 and 5), have been synthesised and the evolution of their structures with changing length of the dicarboxylate ligand was examined. Compounds in the Mn 2(CO2(CH2)nCO2)(OH) 2 series contain 2 dimensionally inorganically connected layers, which are bridged in the third dimension by the dicarboxylate ligand. While the compounds in this series with n = 0 or 2 contain only octahedrally coordinated Mn, the frameworks with longer ligands, n = 4 or 5, have a 1:1 ratio of octahedrally and trigonal bipyramidally coordinated cations. Structures in the Mn4(CO2(CH2)nCO2) 3(OH)2 series contain inorganically connected double chains of MnOx polyhedra, which comprise an equal number of octahedra and trigonal bipyramids. Trigonal bipyramidal coordination environments are very rarely found in dicarboxylate frameworks and the roles of the longer dicarboxylate ligands and the d5 electronic configuration of Mn 2+ in their formation are discussed. The magnetic properties of Mn2(CO2(CH2)2CO2)(OH) 2 have also been examined. It undergoes two magnetic transitions. The higher temperature transition to a two dimensionally ordered antiferromagnetic phase occurs around 44 K, in low applied fields, and is followed by a transition to a three dimensionally ordered canted antiferromagnetic state near 36 K. The Néel temperature of this phase is unusually high for a transition metal dicarboxylate and the factors thought to support this are examined. © The Royal Society of Chemistry 2011.